Architectural graphic standards - Ramsey, Charles G. 1884-1963. (John Wiley and Sons, 2000)
General planning and design data. Sitework. Concrete. Masonry. Metals. Wood and plastics. Thermal and moisture protection. Doors and windows. Finishes. Specialties. Equipment. Furnishings. Special construction. Conveying systems. Mechanical. Electrical. Sports and game facilities...